Zinc-Catalyzed Transacetalization of N,O-Acetals into N,N-Acetals with Benzotriazoles, Indazoles, and Azides - Shin, Sang Ik; Nguyen, Nguyen H.; Im, Jangbin; Shin, Seunghoon (Synlett, 2021)
N,O-Acetals obtained from β-oxidation of ynamides underwent transacetalization with benzotriazoles, leading to N,N-acetals. The Zn(OTf)2 efficiently catalyzed the process, and the reaction is further accelerated in hexafluoroisopropanol, providing a single N1-regiosiomer. The transacetalization conditions developed could be extended to other N-donors, such as 1H-indazole and TMSN3 to afford the corresponding N,N-acetals.
Keywords: Zn catalysis; transacetalization; N,N-acetal; ynamide; benzotriazole